Analysis of ischaemic heart disease risk factors among patients in over forty years of age - Cegła, Bernadeta; Federowicz, Genowefa; Filanowicz, Małgorzata (Polish Journal of Public Health, 2011)
Introduction. Risk factors are human traits increasing the likelihood of heart and vascular diseases. They can be classified into independent and dependent upon the patient. Subjective factors are also called modifiable and include overweight, obesity, arterial hypertension, increased level of cholesterol and lack of physical activity. Studying these factors and analyzing their frequency will enable undertaking targeted educational initiatives improving patients’ lifestyles. Aim. The purpose of the study was to examine: • Modifiable risk factors for ischaemic heart disease (IHD) occurring in people over forty hospitalized in the cardiological ward, • Types of risks prevailing in patients in question, • The degree of their prevalence in women and men. Material and methods. Research group comprised 103 individuals between 40 and 70 with a diagnosed IHD and 105 individuals in control group not diagnosed with the disease. The criterion for inclusion in the study group was IHD diagnosis and taking cardiac medicines. Investigations were conducted at the cardiological ward of the John Paul II District Hospital in Bełchatów. The authors used their own survey as the research tool. Results. Results of the analysis indicated that the risk factor most frequently occurring among study group patients was overweight/obesity. It was identified among 79 individuals. The second factor determined among 75 subjects was arterial hypertension and the third one was increased level of cholesterol. Abdominal obesity occurring significantly more often among women than men was identified in 32 women and 14 men. Conclusions. Overweight/obesity is the most common IHD risk factor identified in patients hospitalized in the cardiological ward at the District Hospital in Belchatow. Abdominal obesity occurs more often among women than men in the research group. People over forty not affected by IHD suffer from arterial hypertension less frequently than IHD patients. Individuals not affected by IHD smoke more often that those who suffer from the disease.